AGAMA POPULER: POTRET GERAKAN FPI DALAM TATAPAN BUDAYA (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2013)
This paper describes how the process freedom of expression by religious groups that often struggle to rekindle the spirit of an impact on the birth of conflict and violence. The main anxiety is the basis of this book is a portrait of FPI activities or actions that are often spread the virus a virus of violence that are smuggled into the language of jihad and struggle. For FPI, jihad as will always be in contact with the violence and destruction. To read the objective reality of the FPI movement , the authors use the approach culture to communication-oriented. In the eyes of intercultural communication, FPI has been done by incorporating the cultural hegemony of the culture wars even thugs who often fly the flag of violence and destruction.